Penerapan Digital Marketing Pada Kedai Cimanuk Berbasis Website - Ninik Ninik Haryani; Listiarini Edy Sudiati; Ngasri . (Electro Luceat, 2020)
Digital marketing is one of the media that is currently in great demand by the community as well as a support in daily activities. Slowly, many people are starting to leave conventional marketing methods and switch to digital marketing. Cimanuk shops must pay attention to the marketing strategy side to encourage and build consumers to make purchasing decisions to meet their needs and wants. The system built is a digital marketing system, with this system it can increase marketing reach to a wider range. With the digital marketing system, it is hoped that the Cimanuk shop will have no difficulty in promoting, informing, updating the latest news and serving customers and can help customers make the order process quickly and make it easier for customers to get more complete information.